Global prevalence of hypertension in children: A systematic review and meta-analysis - Song, P; Zhang, Y; Yu, J; Zha, M; Zhu, Y; Rahimi, K; Rudan, I (American Medical Association, 2019)
Importance: Reliable estimates of the prevalence of childhood hypertension serve as the basis for adequate prevention and treatment. However, the prevalence of childhood hypertension has rarely been synthesized at the global level.